2018
DOI: 10.1186/s13063-018-2651-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient consent to publication and data sharing in industry and NIH-funded clinical trials

Abstract: BackgroundParticipants are recruited into clinical trials under the assumption that the research will contribute to medical knowledge. Therefore, non-publication trials—and, more recently, lack of data sharing—are widely considered to violate the trust of trial participants. Existing practices regarding patient consent to publication and data sharing have not been evaluated. Analyzing informed consent forms (ICFs), we studied what trial participants were told regarding investigators’ intention to contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…While consent seems to be a crucial issue for trial participants, an analysis of 98 informed consent forms found that only 6 (4%) indicated a commitment to share deidentified IPD with third party researchers. 44 Commitments to share were more common in publicly funded trials than in industry-funded trials (7% vs 3%).…”
Section: Resultsmentioning
confidence: 99%
“…While consent seems to be a crucial issue for trial participants, an analysis of 98 informed consent forms found that only 6 (4%) indicated a commitment to share deidentified IPD with third party researchers. 44 Commitments to share were more common in publicly funded trials than in industry-funded trials (7% vs 3%).…”
Section: Resultsmentioning
confidence: 99%
“…Other analyses explored the actual commitment to IPD sharing. Very few (5%) of the studies registered at ClinicalTrials.gov in 2016–2017 by high-volume registrants provided a data-sharing plan [ 36 ] and only 4% of the consent forms of a sample of antibiotic studies, both from public and industry funders, reported a commitment to share IPD [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, how data were collected or processed can affect the way they are shared. Sharing initiatives concerning data collected from human subjects are influenced by informed consent (Spence et al, 2018;White et al, 2020). This can also be affected by processing activities such as anonymization, de-identification, and pseudonymization.…”
Section: What Does An Idg Framework For Neuroscience Look Like?mentioning
confidence: 99%